2022
DOI: 10.7570/jomes22024
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Fact Sheet in Korea, 2021: Trends in Obesity Prevalence and Obesity-Related Comorbidity Incidence Stratified by Age from 2009 to 2019

Abstract: Background:The global public health burden of obesity has increased with socio-economic development. The Korean Society for the Study of Obesity released the 2021 Obesity Fact Sheet to address trends in obesity prevalence and comorbid conditions by different age groups. Methods: Individuals ≥20 years old who underwent a health checkup provided by the Korean National Health Insurance Service between 2009 and 2019 were included. The prevalence of obesity and abdominal obesity was standardized by age and sex base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 25 publications
0
61
0
4
Order By: Relevance
“…According to an obesity fact sheet of the Korean Society for the Study of Obesity, the prevalence of obesity and abdominal obesity has increased for the entire population over the past 11 years (2009 to 2019: obesity from 29.7% to 36.3% and abdominal obesity from 19.3% to 23.9%), particularly in individuals in their 20s (2009 to 2019: obesity from 18.5% to 28.9% and abdominal obesity from 9.0% to 15.6%) and 30s (2009 to 2019: obesity from 22.9% to 32.5% and abdominal obesity from 15.8% to 24.6%) ( Fig. 1B ) [ 9 ].…”
Section: Changes In the Prevalence Of Diabetes And Obesity In Korean ...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to an obesity fact sheet of the Korean Society for the Study of Obesity, the prevalence of obesity and abdominal obesity has increased for the entire population over the past 11 years (2009 to 2019: obesity from 29.7% to 36.3% and abdominal obesity from 19.3% to 23.9%), particularly in individuals in their 20s (2009 to 2019: obesity from 18.5% to 28.9% and abdominal obesity from 9.0% to 15.6%) and 30s (2009 to 2019: obesity from 22.9% to 32.5% and abdominal obesity from 15.8% to 24.6%) ( Fig. 1B ) [ 9 ].…”
Section: Changes In the Prevalence Of Diabetes And Obesity In Korean ...mentioning
confidence: 99%
“…Diabetes screening were previously recommended annually in adults aged ≥40 years regardless of the presence of risk factors and in adults aged ≥30 years with any of the risk factors [ 6 ]. However, it has recently been reported that the prevalence of obesity and/or abdominal obesity, which are major risk factors for diabetes, as well as diabetes has increased in adolescents and young adults [ 2 , 7 - 9 ]. Therefore, in this review, the Clinical Practice Guidelines Committee of the KDA presents a position statement on the screening of diabetes and the current evidence.…”
Section: Introductionmentioning
confidence: 99%
“…노인의 복부비만 유병률도 지속적으로 증가하고 있다. 특히 복 부비만은 체질량지수 기반의 비만과는 달리 80세 이상에서도 지 속적으로 증가하는 모습을 보이며 2019년 기준으로 복부비만의 유병률은 60대 이상은 30.0%, 70대 이상은 36.9%, 80대 이상은 37.4%로 보고되었다 [4]. 위한 다양한 검사방법이 존재하는데, 임상에서는 생체전기저항 분석법(bioimpedance analysis, BIA) 또는 이중에너지엑스선흡수 법(dual energy X-ray absorptiometry) 등의 방법을 흔히 사용하 며 경우에 따라서 컴퓨터단층촬영, 자기공명영상 등도 사용할 수 있다(Table 1) [3].…”
Section: 유병률unclassified
“…Obesity is known to be independently related to air pollution [ 6 , 9 , 10 ]. The prevalence of obesity among Korean adults increased steadily over the past few years, from 29.7% in 2009 to 36.3% in 2019 [ 11 ]. Previous studies have reported that exposure to air pollution may increase the risk of perivascular and peribronchial inflammation, and may increase both systemic inflammation and oxidative stress, which are the main links between air pollution and obesity [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%